2020
DOI: 10.1177/2150132720961255
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Antibiotic Use and Resistance in Jordanian Community

Abstract: Background The public awareness toward the causes and consequences of antibiotic resistance (AR) is crucial to mitigate the inappropriate use of antibiotics (ABs), particularly in the low- and middle-income countries. There was no previous study that assessed the awareness, attitude, and knowledge about antibiotic use and AR among the Jordanian public in affluent and deprived areas. Objective This study aimed to assess the awareness, attitude, and knowledge about antibiotic use and AR in affluent and deprived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
2
18
1
1
Order By: Relevance
“…As in our study, studies globally show that the general public agree that antibiotic overuse contributes to antibiotic resistance,18 23 24 but far fewer understand about the spread of AMR,18 23 24 or think they can influence antibiotic use or AMR 25 26. There is higher misunderstanding about AMR, and the benefit of antibiotics in surveys in Africa and Asia,25 27–31 than in this UK study. A qualitative study with ‘diverse ethnic communities’ in Australia echoed many of the findings in our BAME participants, that is, lack of knowledge of and use of antibiotics, and mistrust in doctors who do not prescribe antibiotics32; the diverse ethnic communities additionally reported that poor antibiotic prescribing and overuse was normal in their home countries32; we did not ask participants about antibiotic practices in their native country.…”
Section: Discussionsupporting
confidence: 43%
“…As in our study, studies globally show that the general public agree that antibiotic overuse contributes to antibiotic resistance,18 23 24 but far fewer understand about the spread of AMR,18 23 24 or think they can influence antibiotic use or AMR 25 26. There is higher misunderstanding about AMR, and the benefit of antibiotics in surveys in Africa and Asia,25 27–31 than in this UK study. A qualitative study with ‘diverse ethnic communities’ in Australia echoed many of the findings in our BAME participants, that is, lack of knowledge of and use of antibiotics, and mistrust in doctors who do not prescribe antibiotics32; the diverse ethnic communities additionally reported that poor antibiotic prescribing and overuse was normal in their home countries32; we did not ask participants about antibiotic practices in their native country.…”
Section: Discussionsupporting
confidence: 43%
“…The percentage of the respondents in this study who reported using antibiotics in the previous month, in the previous 6 months, and a year ago (28.4%, 30.1%, and 9.8%, respectively) was lower than that of the general public in low-income countries (e.g., Egypt, Sudan, and Indonesia), as reported by a WHO multicountry survey [ 2 ]. In comparison with prior studies conducted in Jordan [ 25 , 42 ], the current study’s finding of a general decrease in antibiotic use can be attributed to the increased level of knowledge of antibiotics and antibiotic resistance, stringent public health measures (e.g., promoting social distancing measures), and increasing antibiotic use and resistance awareness programs. Additionally, as a result of public health prevention initiatives and the availability of telemedicine, people are attending outpatient clinics less frequently [ 43 ].…”
Section: Discussioncontrasting
confidence: 83%
“…Previous research revealed that the Jordanian community has a general lack of information and awareness about antibiotic use and antibiotic resistance [ 42 ]. The current study, on the other hand, found that the participants were well aware of potential solutions to the problem of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…31 Public awareness of antibiotic resistance is indispensable to mitigate this insidious problem. [39][40][41] As the World Health Organization (WHO) emphasized, the behavioral change towards the irrational use of antibiotics, otherwise any new addition to the antibiotic will become ineffective. 42 To understand the current public perception and habits, KAP-based studies on antibiotic prescribing, consumption, and antibiotic resistance are conducted in different countries on diverse groups, including medical students, university students, health workers, and common public.…”
Section: Introductionmentioning
confidence: 99%